Thoracic Duct Injury in a Patient Undergoing Axillary Lymphadenectomy: A Case Report - Michelle Albano Ferreira; Juliana Oliveira Costa; Juliana Lopes de Aguiar Araújo; Kleyton Santos de Medeiros; Larissa dos Santos Lourenço Ferreira; Ubiratan Wagner de Sousa; Macerly Layse de Menezes Dantas; Diana Taissa Sampaio Marinho Navarro (Case Reports in Medicine)
A 56-year-old female patient, with no significant comorbidities, presented with abnormal breast exam findings. Imaging revealed a 5.4-cm irregular nodule in the left breast, diagnosed as invasive breast carcinoma (NST, Grade 2). Neoadjuvant chemotherapy was initiated, leading to a reduction in lesion size. Surgical intervention included quadrantectomy, sentinel lymph node biopsy, and axillary lymphadenectomy, which revealed residual carcinoma and positive lymph nodes. Postoperatively, chylous drainage through a Portovac drain was observed, prompting reoperation, during which the injured lymphatic duct was identified. Conservative management with medium-chain triglycerides resulted in a progressive reduction of drainage. The patient was discharged on the 13th postoperative day, subsequently underwent adjuvant radiotherapy, and is currently receiving regular outpatient follow-up.